STRATEGI MENINGKATKAN DAYA SAING PRODUK KERAJINAN ROTAN DI DESA PIANTUS KECAMATAN SEJANGKUNG - Sri Deti; Zulkan; Padila (Lunggi Journal, 2025)
This research is motivated by the fact that the majority of Piantus Village residents from each family can make rattan crafts, counting around 25 more craftsmen than the total number of families in Piantus Village, 561. The proceeds from the sale of rattan craft products from Piantus Village, Sejangkung District, Sambas Regency, are a source of income for local community and able to absorb a number of workers in the area. To be able to implement a product competitiveness program for the rattan craftsman community in Piantus Village, several strategies are needed, especially in increasing the competitiveness of rattan craft products. Based on the research results, it can be concluded that the factors that influence the competitiveness of rattan craft products in Piantus Village, District. Sejangkung are Location, Price, Service, Quality and Promotion. Meanwhile, strategies for increasing the competitiveness of rattan craft products in Piantus Village, District. Sejangkung, there are several strategies implemented, namely: 1) From the central government through the Indonesian Ministry of Industry by providing assistance with rattan peeling machines to craftsmen in Piantus Village, 2) From the regional government, namely by establishing a gallery or what is called a rattan house, apart from that the government regional departments through related agencies such as the Department of Cooperatives, SMEs, Industry and Trade, the Department of Tourism, Youth and Sports also provide training to rattan craftsmen and hold festivals. 3) From the Piantus Village government itself, the strategy implemented is to provide MSME training to rattan craftsmen. 4) From the craftsmen themselves, namely by creating a variety of rattan craft products, promoting rattan craft products through social media such as Facebook, paying attention to product quality in terms of safety and neatness and also bringing or promoting these rattan craft products in various sub-districts and villages. in Sambas district and even to the borders of Indonesia and Malaysia such as Aruk and Serikin